Developing Strategies for an Integrated Ecotourism Business: Study Case in Olele Village, Bone Bolango Regency, Gorontalo, Indonesia - Taufik Usman, Rachmat; M. Baga, Lukman; Sarma, Ma’mun (Business Review and Case Studies, 2022)
The marine ecotourism of Olele Village is one of Indonesia’s tourist destinations with business potential. However, it has not been developed optimally, especially in the fields of facilities and infrastructure, also community empowerment programs. This study aimed to design policy strategies and analyzed integrated ecotourism management policies for local economic development. This study used primary and secondary data. The sampling techniques used snowball and purposive sampling. The data analysis used SWOT, BOS (Blue Ocean Strategy), and BMC (Business Model Canvas) analyses. The SWOT analysis results showed several formulations of ecotourism development strategies related to integrated ecotourism management, the collaboration between stakeholders, and the training and development of MSMEs (Micro, Small, and Medium Enterprises). The results of the BOS analysis recommended strategic innovations to make it easier to compete with competitors. Strategic innovations such creating new demand and supply, increasing tourist facilities, lowering prices, and creating markets. The results of the BMC analysis showed the perspective of opportunities and investment strategies in ecotourism-based local economic programs. It can be concluded that policies and strategies to optimize marine ecotourism utilize coral reefs as regional icons for snorkeling and diving activities. Keywords: blue ocean strategy, business, ecotourism, local economy, SWOT